Optimization of postoperative analgesia after adenoidectomy in children - Georgiyants, M.; Pushkar, M.; Vysotska, O. (My University, 2017)
It is known that pharyngalgia is very common after tonsillectomy. It should be emphasized that the intensity of pain after adenoidectomy in children is not less important than after adenotonsillectomy. Despite the availability of standardized pain assessment scales and existing postoperative analgesia recommendations, unresolved postoperative pain still occurs in children. The research included 117 children with an average age of 7.5 ± 0.4 years, who underwent adenoidectomy at the Department of Anesthesiology and Intensive Care of "Regional Children’s Clinical Hospital" of Kharkov city in 2014. Depending on the method of general anesthesia, patients were divided into 3 groups: group I (n = 41) those who received propofol in combination with fentanyl; group II (n = 40) those who received sevoflurane in combination with fentanyl; group III (n = 36) those who received thiopental sodium combined with fentanyl. We monitored the heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, BIS-index, heart rate variability, respiration rate, and SpO2. We determined the levels of cortisol and insulin in the blood serum, glucose level, the ratio of cortisol/insulin was calculated. Assessment of the efficiency of postoperative analgesia was performed using the Wong-Baker FACES Pain Scale («Faces») and the Oucher Scale. The result of analysis of the intensity of postoperative pain determined that at the 1st hour after the operation by the «Faces» and Oucher scales, it was significantly higher in patients of group II compared with the patients of group I and group III. The morning after the operation there was no significant difference in the pain scales, and the number of scale points showed that children from all groups did not have pain. According to the data of ANOVA it was determined that only the patients in group I with indicator ΔBIS-index «intubation – traumatic moment of operation» experienced postoperative pain intensity on the «Faces» scale. A very strong correlation between «cortisol – BIS index» was observed during the traumatic moment of operation and unidirectional positive correlations were seen both between ΔBIS-index «intubation-the traumatic moment of operation» and between the level of cortisolemia (Δcortisol before surgery – the traumatic moment of operation, Δcortisol extubation – the 1st day after the surgery and Δcortisol before surgery – the 1st day after the surgery) and the intensity of postoperative pain by the «Faces» and Oucher scales. The around-the-clock prescribed administration of ibuprofen at dose 10 mg/kg after adenoidectomy provided effective postoperative analgesia. At the 1st hour after the operation lower pain intensity was revealed in patients using propofol in combination with fentanyl by both pain scales. We believe that propofol is able to influence the level of cortisol and assume that due to minimal changes in the level of cortisol during the perioperative period, propofol can reduce the intensity of postoperative pain.
Keywords: Removal of the adenoid vegetations; children; intravenous anaesthesia; inhalation anaesthesia; postoperative pain